SOCIALIZATION OF IMMIGRATION SERVICES AND IMMIGRATION POLYTECHNIC AT SMA NEGERI 1 SUMBAWA BESAR - Rahmawati Nurul Jannah; Devina Yuka utami (Jurnal Abdimas Imigrasi, 2022)
Immigration services are provided by the Immigration Office under the Immigration Directorate of the Ministry of Law and Human Rights. These services cover all processes related to entry, stay and exit of citizens and foreign nationals in a country. In accordance with Law Number 6 of 2011 concerning Immigration, the class II immigration office of TPI Sumbawa Besar has the following tasks: Granting and Supervision of Visas and Stay Permits, Registration of Foreigners, Granting of Citizenship, Provision of Consular Services, Immigration Law Enforcement, Border Control, International Cooperation while its functions are: Controlling the Movement of People, Security Monitoring, Services and Facilitation, Control of Illegal Immigration, Provision of Information, Law Enforcement, Data Management, Policy Implementation. In this activity the Immigration Office Class II TPI Sumbawa Besar together with lecturers and cadets of the Immigration Polytechnic introduced the Immigration Polytechnic as one of the official schools under the Ministry of Law and Human Rights which focuses on the field of immigration.